Temporary Acts and Laws of His Majesty's Province of New Hampshire in New England 9-10 (1761) - (:unkn) unknown (My University, 1761)
An Act for Preventing and Suppressing Riots, Routs, and Other Unlawful Assemblies: Prohibited gathering in numbers of twelve or more and being armed with clubs and other weapons, or any group numbering thirty or more, from unlawfully, riotously, or tumultuously assembling
Keywords: CARRY - INTENT TO COMMIT CRIME